Predictive value of Glycosylated Fibronectin (GlyFn)/Placenta Growth Factor (PlGF) ratio for high-risk pregnancies: a cohort study - Wahyudi Wirawan; Sofie Rifayani Krisnadi; Anita Deborah Anwar; Annisa Dewi Nugrahani (BMC Pregnancy and Childbirth)
Abstract Background Preeclampsia (PE) is a hypertensive disorder in pregnancy involving multiple organ systems, primarily due to impaired placental development during the first trimester. Reduced Placenta Growth Factor (PlGF) and elevated Glycosylated Fibronectin (GlyFn) levels reflect these pathological changes. Combining these biomarkers into a ratio may enhance PE prediction in high-risk pregnancies. Objective To evaluate the GlyFn/PlGF ratio measured at 20–28 weeks of gestation as a predictor of preeclampsia in high-risk pregnancies across four hospitals in West Java, Indonesia, from April–October 2024. Methods This prospective cohort study involved 54 high-risk pregnant women. The GlyFn/PlGF ratio was analyzed at 20–28 weeks to assess predictive accuracy for PE. Results Significant differences were noted between PE and non-PE groups in pre-pregnancy weight (65.54 ± 12.69 vs. 58.53 ± 7.85 kg), BMI (45.52 ± 53.73 vs. 19.84 ± 2.97), and systolic blood pressure (153.50 ± 19.42 vs. 100.80 ± 15.38 mmHg) (P > 0.05). Risk factors such as prior PE (P = 0.01), diabetes mellitus (P = 0.03), and gestational hypertension (P = 0.02) were more frequent in the PE group. A GlyFn cutoff of 34.31 ng/mL showed a 2.5-fold increased PE risk (sensitivity: 83.33%, specificity: 66.67%, AUC: 0.8071). A PlGF cutoff of 26.72 pg/mL was associated with a 6.8-fold increased risk (sensitivity: 72.22%, specificity: 97.22%, AUC: 0.9147). The GlyFn/PlGF ratio cutoff of 1.288 indicated a 28-fold higher PE risk (sensitivity: 77.78%, specificity: 97.37%, AUC: 0.9244). Conclusion The GlyFn/PlGF ratio outperforms individual biomarkers in predicting preeclampsia in high-risk pregnancies, offering a valuable tool for early risk identification and timely intervention.